2016
DOI: 10.1177/0300985816644301
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor and Ki-67 Expression in Canine Gliomas

Abstract: Novel therapies, including molecular targeted therapies, are being developed for the treatment of human gliomas. To use such therapies for canine gliomas, more complete characterization of molecular targets is required. Epidermal growth factor receptor (EGFR) is one such therapeutic target used in human glioma trials, and the Ki-67 labeling index (LI) is a marker of proliferation and a prognostic indicator. The objectives of this cross-sectional study were to evaluate the expression of EGFR and Ki-67 in canine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 39 publications
2
13
0
3
Order By: Relevance
“…These data may be explained by the high proliferative rate of this tumour . This is also confirmed by the elevated expression of Ki‐67 protein, a widely used proliferation marker, in our COM cases as compared to other canine tumours such as mast cell tumours, indolent lymphoma, gastrointestinal stromal tumours, mammary tumours, peripheral nerve sheath tumours and gliomas …”
Section: Discussionsupporting
confidence: 83%
“…These data may be explained by the high proliferative rate of this tumour . This is also confirmed by the elevated expression of Ki‐67 protein, a widely used proliferation marker, in our COM cases as compared to other canine tumours such as mast cell tumours, indolent lymphoma, gastrointestinal stromal tumours, mammary tumours, peripheral nerve sheath tumours and gliomas …”
Section: Discussionsupporting
confidence: 83%
“…However, studies investigating the relationship between ki-67 and EGFR in glioma patients are scarce. Fraser et al reported a moderate correlation between the expression of EGFR and ki-67 LI in the tumor tissues in canine gliomas ( r = 0.47, P = 0.007) 58. We compared ki-67 LI between high-grade and low-grade patients.…”
Section: Resultsmentioning
confidence: 97%
“…Meanwhile, in vivo studies, as showed that infected with AHNAK vectors glioma cells could decrease tumor of xenograft model growth and weight. Considered Ki-67 is a marker of proliferation and a prognostic indicator 30 , we examined the expression of Ki-67-positive cells in the tumors, and Ki-67 low expression was found in overexpression AHNAK group which possibly prompted the ability of proliferation and aggressiveness was decreased in AHNAK overexpression group. In a meta-analysis of human gliomas, Ki-67 overexpression predicted poor progression-free survival and poor overall survival 31 .…”
Section: Discussionmentioning
confidence: 99%